Dickita y alunita en mina Blanquita, Los Menucos. (prov. de Río Negro) - Marfil, Silvina Andrea (2000)
Minerals related to a kaolinized zone in a rhyolitic tuff of Blanquita Mine, (Los Menucos, Río Negro Province) were studied by polarization microscopy, XRD, SEM, TG, DTA, ICP and IR. Dickita and alunite associated with kaolinite were found in this area, which may support an hidrothermal génesis.